Associations between Early Childhood Education and Care (ECEC) attendance, adversity and language outcomes of 2-year-olds. (December 2022) - Lim, Sarah; Levickis, Penny; Eadie, Patricia
Research evidence suggests children experiencing adversity are at risk of language disparities in early childhood. This puts these children at risk of poor language outcomes, perpetuating disadvantage in later development and academic life. This study aimed to investigate associations between Early Childhood Education and Care (ECEC) attendance, hours of attendance and quality in a cohort of 2-year-old children experiencing adversity with their language outcomes at age five. Pregnant women experiencing adversity, based on women meeting two or more of 10 factors on a brief risk factor survey, were recruited from maternity hospitals in Victoria and Tasmania, Australia. At age 2 years, ECEC data was collected via survey, including ECEC attendance, amount of time spent and ECEC quality (using the Australian government's national measure of quality, the National Quality Standard assessment) ( n = 161). At age 5 years, child language outcomes were measured using a standardised language assessment. This data was analysed using logistic regressions and the non-parametric Kruskal–Wallis test to identify associations. After adjusting for potential confounders, we found language scores at age five were higher, on average, for children who attended ECEC at age two compared to those who did not attend. However, hours of attendance and ECEC quality, was not found to be associated with language outcomes. Findings suggest ECEC attendance in the early developmental years (birth to age 3 years) may be a protective factor against social disadvantage factors and contribute to positive language development for children experiencing adversity. This information is important for the ECEC sector, policymakers and families to advocate, enable and ensure high-quality ECEC is accessible, particularly for children experiencing adversity.